Bonding technology for semiconductor wafers and structures - Chew, Zong Hui (2014)
Silicon had been a dominant material in the Very Large Scale Integration (VLSI) technology which are commonly used in microprocessors and memory devices. Most III- IV compound semiconductor are direct bandgap materials and are commonly used in optoelectronic application such as in Light Emitting Diodes (LEDs) and photodiodes. It will ideal to integrate both materials into a single bulk substrate which will allow the integrated bulk to conceive significant advantages such as reduction of resistive- capacitive (RC) delay. Thus, allowing further advancement in the optoelectronic development In this work, 2 inch Silicon and Indium Phosphide (InP) wafers were monolithic integrated using plasma assisted direct wafer bonding techniques coupled with sequential step annealing in high vacuum. High specific bond energy of 1603m j/m2 was attained. Characterization by optical transmission imaging also illustrates few air bubbles and defects were present in the bonding interface. This work realized a monolithic integrated substrate of different materials on which optoelectronics and microelectronics components can be fabricated.